Eating habits of Brazilian athletes during the Coronavirus pandemic - Dário Capitani, Caroline; Pereira Bacurau, Reury Frank; Chaparro, Fernanda; de Assumpção, Daniela; Sousa, Bruna; Craveiro, Silvio; Moreira, Alexandre; Saldanha Aoki, Marcelo (O Mundo da Saúde, 2022)
The aim of the present study was to evaluate the change in the eating habits of Brazilian athletes during the Coronavirus pandemic. Through a structured online questionnaire, 249 athletes with at least 10 years of practice and/or at least one call by the Brazilian team of their respective modality had their answers analyzed. There was a decrease in the frequency of consumption of vegetables considering the consumption category “5 or more days a week”, with 137 athletes (55.0%) before the pandemic and 113 athletes (45.4%) during the Coronavirus pandemic (p<0.05). The frequency of fruit consumption also showed a reduction, from 150 athletes (60.2%) who consumed fruit “5 or more days a week” before the pandemic to 130 athletes (52.2%) during the pandemic (p<0.05). However, there was an increase in the number of athletes who consumed fried foods (15.3% before to 23.3% during), as well as pizza, snacks, and sandwiches, “2 to 4 days a week” (21.3% before to 31.7% during) (p<0.05) during the Coronavirus pandemic. There was a change in the responsibility of athletes to prepare their meals during the Coronavirus pandemic, as well as a reduction in the frequency of meals taken daily. Although there was an increase in the consumption of ready-to-eat foods during the Coronavirus pandemic (p<0.05), athletes did not increase their consumption of food/meals through apps (p>0.05). In conclusion, the study data demonstrate that Brazilian elite athletes showed changes in eating habits as a result of the Coronavirus pandemic. This fact draws attention, since if maintained for prolonged or intensified periods, the observed changes could be characterized by the worsening of the dietary profile of Brazilian athletes.